Electrolyte and application thereof in dual-ion battery
By using alkylthiophenesulfonamide electrolyte additives in dual-ion batteries, the solvation structure of Li+ is changed, and the side reaction problems caused by high-voltage embedded reactions in dual-ion batteries are solved, which significantly improves the cycling performance and stability of the battery.
Patent Information
- Application Number
- CN202411716031.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-14
AI Technical Summary
The intercalation reaction of anions in graphite materials in dual-ion batteries occurs in the high-voltage range, resulting in electrolyte decomposition, graphite layer peeling and other side reactions, increasing irreversible capacity and deteriorating battery stability.
The alkylthiophenesulfonamide electrolyte additive is used to change the solvation structure of Li+ in the electrolyte to form a thin and uniform interface film, optimize the composition of the positive and negative electrode interfaces, protect the graphite positive electrode and promote the uniform deposition of lithium.
The cycling performance and rate performance of dual-ion batteries have been significantly improved, the battery life has been extended, the capacity retention rate remains high under high current density, and the Coulomb efficiency is stable at more than 97%.
Smart Images

Figure CN119447465A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to an electrolyte and an application thereof in a dual-ion battery. Background Art
[0002] Energy is closely related to human beings and plays an indispensable role in the development of human society. Since coal and oil were used as energy, the economies of countries around the world have developed rapidly. However, energy problems have also begun to emerge. With the continuous acceleration of human development, the consumption rate of coal, oil and natural gas has continued to increase, but the formation of these fossil energy sources requires special conditions and more than five years. Once exhausted, they will be non-renewable. In addition, the environmental problems caused by the use of fossil energy also seriously affect human life. Therefore, changing the energy supply structure and finding new renewable energy sources are the key to solving the growing energy demand.
[0003] Chemical energy is a device that can directly convert chemical energy into electrical energy. Among them, secondary batteries have the functions of clean and efficient energy storage and conversion. Among secondary batteries, dual-ion batteries (DIBs) have attracted widespread attention due to their wide operating voltage, good safety, high energy density, simple design, low cost and other advantages, and have the potential to become a new generation of energy storage devices. At present, the positive electrode materials used in DIBs are mostly graphite. When the charging reaction occurs, the positive electrode undergoes a reaction in which anions are embedded in the graphite. At the same time, the graphite material is oxidized, and cations (such as Li+) are embedded in the negative electrode of the battery; and during the discharge process, the embedded anions and cations return to the electrolyte. In DIBs, both cations and anions can act as active substances. However, the embedding reaction of anions in graphite materials occurs in the high-voltage range (4.5~5.2 V vs. Li / Li+), which exceeds the electrochemical window of common carbonate electrolyte systems. Therefore, a series of side reactions occur under high voltage, such as decomposition of the electrolyte, exfoliation of the graphite layer, and some side reactions that have not yet been discovered, thereby increasing the irreversible capacity and deteriorating the stability of the battery.
[0004] Lithium metal is considered to be an ideal anode for next-generation secondary batteries, as it has the lowest electrochemical potential (−3.04 V relative to standard hydrogen electrode) and the highest theoretical specific capacity (3860 mAh g -1), has received widespread attention in high-energy-density DIBs. However, due to the high reactivity between the lithium metal anode and the electrolyte, the practical application of the lithium metal anode is also affected by poor cycle life and safety hazards. Due to the uneven and fragile solid electrolyte interface (SEI) formed by the decomposition of the electrolyte, lithium dendrites and "dead lithium" grow in large quantities, lithium metal and electrolyte are rapidly consumed, capacity decays, and coulombic efficiency (CE) is low, eventually leading to battery failure. During the repeated lithium plating / stripping process, the formed lithium dendrites may also pierce the diaphragm, causing the positive and negative electrodes of the battery to contact, causing safety hazards such as battery short circuit and thermal runaway.
[0005] As one of the key components of batteries, electrolyte engineering is crucial to solving the above problems. Electrolyte engineering can essentially adjust the electrode / electrolyte interface composition and battery performance by adjusting the solvation structure of Li+. Advanced electrolyte systems such as high-concentration electrolyte (HCE), local high-concentration electrolyte (LHCE), and electrolyte additives have been proposed and proven to effectively improve the electrode / electrolyte interface quality, promote good lithium morphology, and extend battery life. However, the high viscosity and poor wettability of HCE limit its wide application. The addition of diluents with a lower coordination number with Li+ to LHCE reduces the salt concentration and viscosity while ensuring a solvation structure similar to HCE, but its long-term electrochemical stability is not ideal and needs further improvement. Although many electrolyte strategies explored by predecessors have made significant progress in improving battery safety and performance, they face great challenges in meeting the practical application requirements of DIBs.
[0006] As the most economical and effective strategy in electrolyte engineering, electrolyte additives have good application prospects in solving the above problems. Therefore, the research and development of electrolyte additives with better performance is of great significance to improving the capacity and cycle performance of dual-ion batteries. Summary of the invention
[0007] In view of this, the present invention provides an electrolyte additive and its application in a dual-ion battery, which can improve the capacity and cycle performance of the dual-ion battery.
[0008] The technical solution of the present invention is as follows: An electrolyte comprises an electrolyte, an organic solvent and an electrolyte additive, wherein the electrolyte additive is an alkylthiophene sulfonamide additive and the amount of the electrolyte additive in the electrolyte is 0.01 M to 0.5 M.
[0009] Preferably, the electrolyte is one of lithium hexafluorophosphate, lithium tetrafluoroborate, potassium hexafluorophosphate or sodium hexafluorophosphate, preferably lithium hexafluorophosphate.
[0010] Preferably, the organic solvent comprises one or more of ethylene carbonate, ethyl methyl carbonate, vinylene carbonate and fluoroethylene carbonate, preferably ethyl methyl carbonate.
[0011] Preferably, the electrolyte additive includes one of vinylene carbonate, lithium nitrate, 2-thiophenesulfonamide, N-methyl-2-thiophenesulfonamide, N-ethyl-2-thiophenesulfonamide, N-isopropyl-2-thiophenesulfonamide, N-tert-butyl-2-thiophenesulfonamide, and N,N-diethyl-2,2,3,3-tetrafluoropropionamide; preferably one of 2-thiophenesulfonamide, N-methyl-2-thiophenesulfonamide, N-ethyl-2-thiophenesulfonamide, N-isopropyl-2-thiophenesulfonamide, and N-tert-butyl-2-thiophenesulfonamide.
[0012] Preferably, the amount of the electrolyte additive in the electrolyte is 0.01 M to 0.1 M.
[0013] The present invention adopts the alkylthiophene sulfonamide additive as an electrolyte additive, which can change the solvation structure of Li+ in the electrolyte, thereby changing the composition of the electrode electrolyte interface film to form a thin and uniform interface film. The additive molecules have a strong binding ability with Li+, and are more likely to enter the solvation sheath of Li+ to form a unique solvation structure. Moreover, due to the low LUMO orbit and the high HOMO orbit, the additive molecules will preferentially decompose on the positive and negative electrodes to form a multiphase inorganic interface film rich in LiF, Li3N and Li2S, which has the effect of simultaneously optimizing the positive and negative electrode interfaces of the DIB, can protect the graphite positive electrode, and induce the uniform deposition of lithium, thereby improving the performance of the dual ion battery.
[0014] In addition, the electrolyte of the present invention has simple components, consisting of a single lithium salt, a single solvent and a trace amount of electrolyte additives, which can reduce the occurrence of side reactions and reduce production costs. Only a single trace amount of thiophene sulfonamide additives is added to change the solvation structure of the electrolyte and thus adjust the composition of the interface film, greatly improving the cycle performance and rate performance of the dual-ion battery.
[0015] The embodiment of the present invention also provides a use of the above-mentioned electrolyte in a dual-ion battery.
[0016] Preferably, the dual-ion battery comprises a positive electrode, a negative electrode, and a separator. The negative electrode comprises a negative electrode current collector and a negative electrode material. The negative electrode current collector serves as a negative electrode main material, and the negative electrode material comprises lithium metal.
[0017] Preferably, the positive electrode comprises a positive electrode current collector and a positive electrode material, the positive electrode material comprises a positive electrode active material, and the positive electrode active material comprises a graphite material.
[0018] Preferably, the voltage of the dual-ion battery is 3.0 V to 5.0 V.
[0019] Preferably, the current density of the dual ion battery is 50 mA g -1 ~3000 mA g -1 .
[0020] Compared with the prior art, the electrolyte concentration in the dual-ion battery provided by the present invention is higher. The increase in electrolyte concentration increases the number of conductive ions, and the battery capacity and rate performance are greatly improved. In addition, the present invention adds an electrolyte additive that can change the solvation structure of Li+ in the electrolyte and decompose at the positive and negative electrodes of the battery, forming a layer of stable CEI and SEI film on the surface of the electrode material, effectively improving the stability of the battery.
[0021] The test shows that the dual-ion battery provided by the present invention can achieve 700 cycles at a current density of 2 C with a capacity retention rate of 86%. At an ultra-high current density of 10 C, the cycle can reach 1800 cycles with a capacity retention rate of 92%, the coulombic efficiency remains stable at more than 97%, and the energy density is as high as 404 Wh kg −1 , greatly improving the cycle life of dual-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 The diagram is the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) energy level diagram of each component of the additive, LiPF6, and EMC used in the electrolyte of the present invention; Figure 2 The SEM image of the electrode surface of the lithium-lithium symmetric battery after cycling for 50 h in Comparative Example 1; Figure 3 This is a SEM image of the electrode surface of the lithium-lithium symmetric battery after cycling for 50 h in Example 1; Figure 4 The graph is a cycle stability diagram of the dual-ion battery of the present invention having the electrolyte additives of Example 1 and Comparative Example 1 at a current density of 2 C (1 C=100 mA g-1); Figure 5 Graph showing the cycle stability of the dual-ion battery of the present invention having the electrolyte additives of Example 1 and Comparative Example 1 at a current density of 10 C; Figure 6The XPS S 2p spectra of the lithium negative electrode of the dual ion battery of the present invention having the electrolyte additives of Example 1 and Comparative Example 1 after 10 cycles; Figure 7 The N 1s spectrum of the lithium negative electrode XPS of the dual ion battery of the present invention having the electrolyte additives of Example 1 and Comparative Example 1 after 10 cycles; Figure 8 The graphite surface XPS S 2p spectra of the dual ion battery of the present invention having the electrolyte additives of Example 1 and Comparative Example 1 after 10 cycles; Fig. 9 This is the N 1s spectrum of the graphite surface XPS of the dual ion battery of the present invention having the electrolyte additives of Example 1 and Comparative Example 1 after 10 cycles; Fig.10 is the RDF spectrum of the electrolyte of Comparative Example 1 of the present invention; Fig.11 This is the RDF spectrum of the electrolyte of Example 1 of the present invention. DETAILED DESCRIPTION
[0024] To make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0025] The dual-ion battery and electrolyte additive according to the embodiment of the present invention are described in detail below.
[0026] The invention provides a novel dual-ion battery, comprising a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte.
[0027] The positive electrode includes a positive electrode current collector and a positive electrode material, the positive electrode material includes a positive electrode active material, and the positive electrode active material includes a graphite material. The graphite positive electrode is graphite well known to those skilled in the art, and the present invention has no special restrictions on its source, and commercially available products can be used.
[0028] The negative electrode comprises a negative electrode current collector and a negative electrode material. The negative electrode current collector serves as a negative electrode main material, and the negative electrode material comprises a metal lithium sheet.
[0029] The electrolyte comprises an electrolyte, an organic solvent and an electrolyte additive; The organic solvent of the present invention comprises one or more of ethylene carbonate, ethyl methyl carbonate, vinylene carbonate and fluoroethylene carbonate, preferably ethyl methyl carbonate.
[0030] The electrolyte of the present invention is one of lithium hexafluorophosphate, lithium tetrafluoroborate, potassium hexafluorophosphate or sodium hexafluorophosphate. Preferably, the electrolyte is lithium hexafluorophosphate.
[0031] The electrolyte additive includes one of vinylene carbonate, lithium nitrate, 2-thiophenesulfonamide, N-methyl-2-thiophenesulfonamide, N-ethyl-2-thiophenesulfonamide, N-isopropyl-2-thiophenesulfonamide, N-tert-butyl-2-thiophenesulfonamide, N,N-diethyl-2,2,3,3-tetrafluoropropionamide, etc. Preferably, it is one of 2-thiophenesulfonamide, N-methyl-2-thiophenesulfonamide, N-ethyl-2-thiophenesulfonamide, N-isopropyl-2-thiophenesulfonamide, and N-tert-butyl-2-thiophenesulfonamide; Preferably, the amount of the electrolyte additive in the electrolyte is 0.01 M to 0.5 M, more preferably 0.01 M to 0.1 M.
[0032] The alkylthiophene sulfonamide additives of the present invention have the following two properties: (1) they have a higher HOMO orbital and a lower LUMO orbital, and can be preferentially oxidized and decomposed at the positive and negative electrodes; and (2) they have a strong affinity with Li+ in the electrolyte. Both of these characteristics are conducive to the electrolyte additive entering the solvation structure of lithium ions, preferentially decomposing on the lithium negative electrode and the graphite positive electrode to form inorganic phases rich in N and S to stabilize SEI and CEI, induce uniform deposition of lithium, protect the graphite positive electrode, and greatly improve the cycle performance of the battery.
[0033] In order to further illustrate the present invention, the following examples are provided for detailed description. Example 1 In a glove box, weigh an appropriate amount of electrolyte additive NTSA (N-tert-butyl-2-thiophenesulfonamide) and add it to the commercially available basic electrolyte for dual-ion batteries (4M LiPF6+EMC; purchased from Duoduo Chemical Technology Co., Ltd.) and stir evenly.
[0034] Comparative Example 1 The electrolyte provided in this comparative example is a commercially available basic electrolyte (4M LiPF6+EMC: purchased from Duoduo Chemical Technology Co., Ltd.) The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy level diagrams of each component were obtained by using quantum chemistry simulation calculations for all components in the electrolyte. The calculation results are shown in Figure 1As shown, the electrolyte additive NTSA has the highest HOMO (-6.782 eV) and lowest LUMO (-1.231 eV) energy levels compared with other components of the electrolyte EMC and LiPF6, which indicates that compared with other solvent molecules, the electrolyte additive will be preferentially oxidized and reduced and participate in the formation of CEI and SEI.
[0035] The lithium-lithium symmetrical battery prepared by the electrolyte of the above-mentioned Example 1 and Comparative Example 1 was subjected to stability test for 50 h and then disassembled to obtain its lithium negative electrode. The surface morphology of the lithium negative electrode was characterized by scanning electron microscopy (SEM). The characterization results are shown in FIG. Figure 2 , Figure 3 The surface of the lithium sheet using the electrolyte of Comparative Example 1 was observed to have loose "dead lithium" and a large amount of lithium dendrites accumulated, and the lithium deposition was very uneven ( Figure 2 ). This loose structure with a high surface area is highly reactive and cannot hinder the penetration of the electrolyte, resulting in continuous consumption of the electrolyte and low reversibility. However, the surface of the lithium sheet using the electrolyte of Comparative Example 1 presents a dense and uniform planar block structure, which can effectively inhibit the growth of lithium dendrites ( Figure 3 ).
[0036] The dual-ion batteries prepared in Example 1 and Comparative Example 1 were subjected to charge and discharge tests, with current densities of 2C and 10C (1C=100mA g -1 ), voltage range: 3V~5V. Test results are shown in Figure 4 , Figure 5 , Figure 4 The figure is a comparison of the cycle stability and coulombic efficiency of the dual ion battery prepared in Example 1 of the present invention and Comparative Example 1 at a current density of 2 C. Figure 4 It can be seen that the dual-ion battery of Comparative Example 1 only starts to fail after 50 cycles, while the battery with the electrolyte of Example 1 still has a capacity retention rate of 86% after 700 cycles, a CE of 90%, and an energy density of 409 Wh kg −1 , showing stable cycling ability. Figure 5 As shown in Figure 1, even at a high rate of 10 C, the battery of Example 1 has an ultra-long life of 1800 cycles and can still provide 72 mAh g after 1800 cycles. -1 The discharge capacity of the battery is 100%, the capacity retention rate is 90%, and the coulombic efficiency remains stable at over 97%, with an energy density of up to 404 Wh kg −1 . It can be seen that it is proved that electrolyte additives can significantly improve the electrochemical performance of lithium-graphite dual-ion batteries.
[0037] After the dual-ion batteries prepared in Example 1 and Comparative Example 1 were cycled for 10 cycles at a current density of 2 C, the graphite positive electrode and the lithium negative electrode were disassembled, and the surface chemical compositions of the lithium metal negative electrode and graphite in different electrolytes were further studied by X-ray photoelectron spectroscopy (XPS). The results are as follows: Figure 6-Figure 9 As shown. Figure 6 As shown in the N 1s spectrum, no N- or S-containing compounds were produced on the surface of the lithium sheet circulating in the electrolyte of Comparative Example 1, except for the NO / NS peak (399.2 eV) that may be caused by the sample being exposed to air. However, Li3N (397.1 eV) appeared in the XPS N 1s of the lithium metal anode circulating in the electrolyte of Example 1. Figure 6 In the S2p spectrum of Example 1, SO4 2- 、SO3 2- The typical characteristic peaks of Li2S (166-171 eV) and Li2S (159-165 eV) are shown in Figure 1. The XPS results show that the electrolyte of Comparative Example 1 can promote the formation of an inorganic rich SEI film containing Li3N and Li-S on the surface of lithium metal. Li3N can make lithium nucleate uniformly and induce lithium uniform deposition. In addition, since Li3N and Li-S have high ionic conductivity, they can inhibit the growth of lithium dendrites. Figure 8 , Fig. 9 XPS spectrum of graphite N 1s ( Figure 8 ) and S2p( Fig. 9 ) showed that after adding NTSA, a CEI film rich in inorganic components such as LiF, Li3N and Li-S was constructed on the graphite surface. Fig.10 , Fig.11 From the RDF spectra of different electrolytes, we can see that the g(r) peak of the O-additive is at 2.17Å, indicating that the trace amount of the added additive appears in the first solvation sheath of Li+, changing the original solvation structure of Li+.
[0038] The above invention applies the electrolyte additive to dual-ion batteries to obtain CEI and SEI rich in Li3N and Li-S, thereby effectively protecting graphite and lithium metal. First-principles calculations show that the electrolyte additive molecules with low LUMO (−6.782 eV) and high HOMO (1.213 eV) can easily decompose on the surface of the lithium metal negative electrode and the graphite positive electrode to form SEI and CEI of Li3N and Li-S, which can effectively inhibit the growth of lithium dendrites and the collapse of the graphite structure. At a current density of 2 C, 700 cycles were achieved with a capacity retention rate of 86%; at an ultra-high current density of 10 C, the cycle lasted for 1800 cycles with a capacity retention rate of 92%, and the coulombic efficiency remained stable at more than 97%, with an energy density of up to 404 Wh kg −1, greatly improving the cycle life of dual-ion batteries. Adding an additive that simultaneously regulates the composition of the positive and negative electrodes can protect both the positive and negative electrodes of the battery, thereby extending the battery life. This cost-effective strategy provides a way to explore DIBs as a sustainable fixed energy storage in the future.
[0039] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. An electrolyte comprising an electrolyte, an organic solvent and an electrolyte additive, characterized in that: The electrolyte additive is an alkylthiophene sulfonamide additive, and the amount of the additive in the electrolyte is 0.01 M to 0.5 M.
2. The electrolyte according to claim 1, characterized in that The electrolyte is one of lithium hexafluorophosphate, lithium tetrafluoroborate, potassium hexafluorophosphate or sodium hexafluorophosphate, preferably lithium hexafluorophosphate.
3. The electrolyte according to claim 1, characterized in that The organic solvent includes one or more of ethylene carbonate, ethyl methyl carbonate, vinylene carbonate and fluoroethylene carbonate, preferably ethyl methyl carbonate.
4. The electrolyte according to claim 1, characterized in that The electrolyte additive includes one of vinylene carbonate, lithium nitrate, 2-thiophenesulfonamide, N-methyl-2-thiophenesulfonamide, N-ethyl-2-thiophenesulfonamide, N-isopropyl-2-thiophenesulfonamide, N-tert-butyl-2-thiophenesulfonamide, and N,N-diethyl-2,2,3,3-tetrafluoropropionamide; preferably one of 2-thiophenesulfonamide, N-methyl-2-thiophenesulfonamide, N-ethyl-2-thiophenesulfonamide, N-isopropyl-2-thiophenesulfonamide, and N-tert-butyl-2-thiophenesulfonamide.
5. The electrolyte according to claim 1, characterized in that The amount of the electrolyte additive in the electrolyte is 0.01 M~0.1 M.
6. Use of the electrolyte according to any one of claims 1 to 5 in a dual-ion battery.
7. The use according to claim 6, characterized in that: The dual-ion battery comprises a positive electrode, a negative electrode and a separator. The negative electrode comprises a negative electrode current collector and a negative electrode material. The negative electrode current collector serves as a negative electrode main material, and the negative electrode material comprises lithium metal.
8. The use according to claim 6, characterized in that: The positive electrode includes a positive electrode current collector and a positive electrode material. The positive electrode material includes a positive electrode active material. The positive electrode active material includes a graphite material.
9. The use according to claim 6, characterized in that: The voltage of the dual-ion battery is 3.0 V to 5.0 V.
10. The dual ion battery according to claim 6, characterized in that: The current density of the dual-ion battery is 50 mA g -1 ~3000 mA g -1 .